Pengujian Parametrisasi Baru Potensial Woods-Saxon dengan Perhitungan Spektrum Tenaga Keadaan Dasar Inti Pb208 - Raden Oktova (Universitas Negeri Surabaya, 2013)
Single-particle and single-hole energy levels in the nucleus Pb208 are calculated using a new parametrization of the Woods-Saxon potential in coordinate space and the Numerov algorithm. The application of the new parameter set proves to be capable of improving the accuracy of the calculation compared to a previous parameter set as measured from the energy standard deviation (relative to the experimental values) only for single-particle levels, but it fails for single-hole levels.